Dipeptidyl peptidase-4 inhibition prevents vascular aging in mice under chronic stress: Modulation of oxidative stress and inflammation. (1st December 2019) - Xin, Minglong; Jin, Xianglan; Cui, Xiangdan; Jin, Chunzi; Piao, Limei; Wan, Ying; Xu, Shengnan; Zhang, Shengming; Yue, Xueling; Wang, Hailong; Nan, Yongshan; Cheng, Xianwu
Abstract: Background and aims: Chronic psychosocial stress is a risk factor for cardiovascular disease. In view of the important role of dipeptidyl peptidase-4 (DPP-4) in human pathophysiology, we studied the role of DPP-4 in stress-related vascular aging in mice, focusing on oxidative stress and the inflammatory response. Methods and results: Male mice were randomly divided into a non-stress group and an immobilization stress group treated for 2 weeks. Chronic stress accelerates aortic senescence and increases plasma DPP-4 levels. Stress increased the levels of gp91 phox, p22 phox, p47 phox, p67 phox, p53, p27, p21, p16 INK4A, vascular cell adhesion molecule-1, intracellular adhesion molecule-1, monocyte chemoattractant protein-1, matrix metalloproteinase-2 (MMP-2), MMP-9, cathepsin S (Cat S), and Cat K mRNAs and/or protein in the aorta of the stressed mice and decreased their levels of endothelial nitric oxide synthase and SirTuin1 (SirT1). DPP-4 inhibitors can improve stress-induced targeting molecules and morphological changes. In vitro, the inhibition of DPP-4 also alleviated the changes in the oxidative and inflammatory molecules in response to hydrogen peroxide in human umbilical vein endothelial cells. Conclusions: DPP-4 inhibition can improve vascular aging in stressed mice, possibly by improving oxidative stress production and vascular inflammation. Our results suggest that DPP-4 may become a new therapeutic target for chronic stress-related vascular aging in metabolic cardiovascular diseases.